Clinical outcomes of patients with multivessel coronary artery disease treated with robot-assisted coronary artery bypass graft surgery versus one-stage percutaneous coronary intervention using drug-eluting stents. Issue 38 (September 2019) - Su, Chieh-Shou; Shen, Ching-Hui; Chang, Keng-Hao; Lai, Chih-Hung; Liu, Tsun-Jui; Chen, Kuan-Ju; Lin, Tzu-Hsiang; Chen, Yu-Wei; Lee, Wen-Lieng
Abstract : Abstract: A number of studies have reported on treatment outcomes of coronary stenting (PCI) for multivessel coronary artery diseases (MVD), and compared them with the conventional coronary artery bypass grafting (CABG). However, the clinical outcomes of robot-assisted CABG (R-CABG) in comparison with PCI in MVD patients have not been investigated. We recruited retrospectively MVD patients receiving R-CABG and PCI with drug-eluting stents for all vessels in one stage between January 2005 and December 2013 at our institution with at least 3 years of outcomes were retrospectively recruited and analyzed. A total of 638 MVD patients were studied. Among them, 281 received R-CABG, and 357 received PCI. Similar complete revascularizations were achieved in both groups (R-CABG: 40.2%, PCI: 41.5%, P = .751). The residual stenosis was 4.1 ± 4.4 in the R-CABG group, and comparably 3.5 ± 3.7 in the PCI group ( P = .077). Patients in the R-CABG group were younger, with more severe coronary artery disease (CAD) and had more background risk factors. The in-hospital and long-term mortalities as well as the incidence of TLR, myocardial infarction (MI), stroke were all similar between groups. But the incidence of TVR and any revascularization were lower in the R-CABG group. The long-term mortality was predicted by age, left ventricular ejection fraction, and chronic kidney disease, but not by the revascularization modality, completeness of revascularization, nor residual SYNTAX scores. The last 3 factors were not predictors of long-term TLR, TVR, MI, and stroke. The in-hospital and long-term survival rates of MVD were similar for both the R-CABG and PCI groups. But the R-CABG group had rates of TVR and any revascularization lower than PCI. Revascularization modality, completeness of revascularization, and residual SYNTAX scores were not predictors of in-hospital and long-term mortalities, MI, and stroke in real-world practice. R-CABG was associated with lower rates of TLR and TVR, and is likely a safe and effective treatment and an alternative choice of PCI for MVD patients who have low surgical risks.